THE EFFECT OF REGIONAL ORIGINAL INCOME (PAD) AND TRANSFER INCOME ON CAPITAL EXPENDITURE (Case Study on District and City Governments in Central Sulawesi Province) - Ngasang, Allika Fitriyah Salsabila; Ridwan, Ridwan; Mattulada, Andi; Jamaluddin, Jamaluddin (Penelitian dan Pengembangan Ilmu, 2025)
This research tends to examine the Influence of Local Original Revenue (PAD) and Transfer Revenue on Capital Expenditure in Regencies/Cities in Central Sulawesi Province. The method used in this study is a quantitative technique with secondary data analysis obtained from the Regional Government Financial Report (LKPD) for the 2021-2023 period. The data analysis technique employed is multiple linear regression to identify the relationship between PAD, transfer revenue, and capital expenditure. The study’s results reveal that PAD has a significantly positive effect on capital expenditure, indicating that increasing PAD encourages higher allocation of capital expenditure. Transfer revenue is also found to have a significantly positive effect on capital expenditure, indicating the important role of fund transfers from the central government in supporting regional development. Generally, this study’s results give implications that PAD management and transfer revenue optimization can be important strategies in increasing capital expenditure capacity for regional development in Central Sulawesi.